Visit-to-Visit Blood Pressure Variability, Neuropathology, and Cognitive Decline - Ma, Yuan (Neurology, 2021)
OBJECTIVE: Large systolic blood pressure (SBP) variability has been proposed as a novel risk factor for dementia above and beyond SBP levels, but the underlying neuropathology is largely unknown. We investigated the relationship among visit-to-visit SBP variability, cognitive deterioration, and underlying neuropathologic changes. METHODS: We used longitudinal data (between 2005 and 2019) from the National Alzheimer's Coordinating Center. A total of 13,284 dementia-free participants ≥50 years of age were followed up over a median of 5.0 (interquartile range 3.1–7.6) years. Neuropathology data were available in 1,400 autopsied participants. Visit-to-visit SBP variability was quantified from repeated annual SBP measurements. Cognitive deterioration was defined as conversion from normal cognition to mild cognitive impairment (MCI) or dementia or from MCI to dementia. RESULTS: Larger visit-to-visit SBP variability was associated with cognitive deterioration (adjusted odds ratio comparing extreme quintiles 2.64, 95% confidence interval 2.29–3.04, p < 0.001). It was also associated with a higher burden of vascular pathology (including microinfarcts, white matter lesions, atherosclerosis of the circle of Willis, and arteriolosclerosis) and with neurofibrillary tangle pathology assessed by Braak staging (all p < 0.05). The association with cognitive deterioration and vascular pathology appeared stronger among those with normal cognition vs those with MCI at baseline. These findings were observed after adjustment for age, sex, mean SBP, and other confounding variables. Similar results were observed for diastolic blood pressure variability. CONCLUSION: Larger visit-to-visit SBP variability was associated with cognitive deterioration. It was also associated with cerebrovascular pathology and neurofibrillary tangles. These results suggest the intertwined role of vascular and Alzheimer disease pathology in the etiology of dementia.